HAPS-based relaying for integrated space-air-ground networks with hybrid FSO/RF communication : a performance analysis - R., Swaminathan (2021)
IEEE Optical wireless communication (OWC) has garnered significant importance to provide gigabit capacity links owing to its unique features. Free space optics (FSO) communication, which is the term used for OWC in outdoor scenario, is a good candidate to establish ground-to-satellite/satellite-to-ground links. Despite of many advantages, FSO communication in uplink is limited by the adverse effects of beam wander, beam scintillation, and pointing errors. Therefore, to counteract the limitations, it is wise to backup FSO links with reliable radio frequency (RF) links. In addition, the complementary characteristics exhibited by FSO and RF links to atmospheric effects have paved the way for hybrid FSO/RF communication. In recent years, a growing interest is also witnessed in the research and development of space-air-ground integrated network (SAGIN). This paper aims to fuse FSO and RF technologies for integrated space-air-ground uplink networks utilizing unmanned aerial vehicle (UAV) such as high altitude platform station (HAPS) as a relay station for achieving better reliability. Thus, we propose single-hop and SAGIN-based dual-hop system models for uplink satellite communication with hybrid FSO/RF links and the performance is investigated using analytical and simulation results. In summary, the results show that hybrid FSO/RF systems perform better than the FSO systems in uplink scenario due to backup RF link.